Steroid-induced diabetes mellitus in pemphigus vulgaris patient at Bali Mandara Hospital: a case report - Felicia Aviana; I Made Birawan (DiscoverSys Inc, 2021)
Background: Pemphigus vulgaris (PV) is a blistering autoimmune disease of the skin and mucous membranes defined histologically by intraepidermal blister due to acantholysis. Systemic corticosteroids and immunosuppressive agents had greatly improved the prognosis of pemphigus. However, steroid use often leads to metabolic complications, such as diabetes mellitus. This case report describes steroid-induced diabetes mellitus in PV, where the side effect of long-term high dosages steroid used and the method to manage it can be used as a study case.Case report: A 31-year-old man complained of new blisters from almost the entire body. He had a history of PV 1 year ago and no history of diabetes mellitus in the patient or family. He had a medication history of methylprednisolone 8 mg every 8 hours. Dermatological status showed erythema macules, extensive erosion almost on the entire body, the Nikolsky sign (+), and the Asboe-Hansen sign (+). Blood laboratory result: random blood glucose 451 mg/dl, HbA1c 12.3%. Histopathological examination: suprabasal blister, in which the basal cells still attached to the basement membrane show a “tombstone” appearance. The diagnosis was steroid-induced diabetes in pemphigus vulgaris. He was treated with steroids and insulin.Conclusion: Steroid use in PV treatment can lead to metabolic complications, such as diabetes mellitus. Regularly monitoring is needed to prevent complications due to steroid use.